Social change for women and children - Demos, Vasilikie P.; Segal, Marcia Texler, 1940- (Advances in gender research ;, 2000)
The contributors to this volume consider policy implications of gender research with an emphasis on its relevance for children - particularly girls; and gender inequality within a range of contexts from that of Cameroon society where basic education is an issue, to that of feminist family settings in the United States.